2006
DOI: 10.1111/j.1439-037x.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Secondary Metabolites Formed by Field Fungi in Autumn‐Saved Herbage

Abstract: Taking into consideration the fact that in recent years weather conditions were sufficient to feed cattle on pasture until late autumn or early winter, an experiment was carried out during the years 2000 and 2003 on a low input pasture to show the effect of the pre-utilization date (June, July, August) and the harvest date in the autumn/winter period (November, December, January) on the accumulation of the following secondary metabolites formed by fungi: ergosterol (ERG), ochratoxin A (OA) and zearalenone (ZEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Golinski et al (2006) arrived at similar conclusions for a grass stand in January. The higher zearalenone content may result from the increasing population of zearalenone-forming soil fungi.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Golinski et al (2006) arrived at similar conclusions for a grass stand in January. The higher zearalenone content may result from the increasing population of zearalenone-forming soil fungi.…”
Section: Discussionsupporting
confidence: 53%
“…The warmer end of the growing season might have related also to the higher production of mycotoxins. On the other hand, at the end of the growing season in 2007, the detected et al (1996), Engels and Krämer (1996), Behrendt et al (2004), Golinski et al (2006) point to a high ergosterol content in forage from a grass stand used in January and documents a high content of zearalenone occurring in connexion with the high ergosterol content in this month.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, higher levels of mycotoxins occurring during winter months were reported by Golinski et al . [ 23 ]. Forage from the beginning of June is generally characterized by low levels of mycotoxins, and this is especially evident ( p < 0.01) for DON and ZEA.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, ERG is more sensitive than another fungal biomarker 'chitin' for the detection of early stage fungal growth [26]. In addition, Japelt et al [27] and Golinski et al [28] reported that ERG contents increase with increasing humidity and decreasing temperatures during fall and winter months, under favourable environmental conditions for the growth of moulds.…”
mentioning
confidence: 99%